Detection of Campylobacter in human faecal samples in Fiji - Aruna Devi; Jenny Wilkinson; Timothy Mahony; Thiru Vanniasinkam (World Health Organization Regional Office for the Western Pacific, 2014)
Introduction: Data on campylobacteriosis in developed countries are well documented; in contrast, few studies on campylobacteriosis have been conducted in developing countries. This study was undertaken to test for Campylobacter in human faecal samples sent to the two major pathology laboratories in Fiji. Methods: A total of 408 diarrhoeal faecal samples were collected from the two major hospital pathology laboratories in Central Fiji (Suva) and Western Fiji (Lautoka) between December 2012 and February 2013 and from June to July 2013. Samples were analysed for the presence of Campylobacter using polymerase chain reaction (PCR) based methods. Results: Campylobacter was detected in 241/408 (59.1%) of samples tested using PCR. Samples from children aged less than five accounted for 21.6% of positive cases. Discussion: Campylobacter was detected in 59.1% of diarrhoeal samples collected from the two main laboratories in Fiji. A high proportion of children under five years with Campylobacter has been reported in other countries and could be due to parents being more likely to seek medical attention. Further studies are required to confirm the species of Campylobacter that are predominantly associated with gastroenteritis in Fiji.